ISLAM DAN SASTRA MELAYU KLASIK - Rusdin Rusdin (State Institute of Islamic Studies (IAIN) Palu, 2005)
The advent of Islam in the archipelago in the 7th century has given a positive impact on the development of many fields of life. One of them is the development of Malaya literature in this area. Ar-Raniri, a great ulama of Aceh sultanate, serves as one of Muslim poets who, in 1638 B.C., wrote not only works on Islam but also on a work of Malaya literature, that is Bustan al-Salatin (Garden of Kings). This work was written by him because of Sultan Iskandar Sani’s order. Another work of Malaya literature can be mentioned here is Taj al-Salatin (Crown of Kings) written by Bukhari al-Jauhari in 1603 B.C. Centers for Malaya literature in the archipelago are Aceh, Malacca, and Johor-Riau. Kata Kunci: Islam, sastra Melayu klasik